ОРОЛБЎЙИ МИНТАҚАСИ УЧУН ИНСОН ХАВФСИЗЛИГИ БЎЙИЧА КЎП ТОМОНЛАМА ШЕРИКЛИК ТРАСТ ЖАМҒАРМАСИ - Абдимўминов, О.Б. (SCIENCE and SOCIETY, 2025)
This article discusses the activities of the UN Multilateral Partnership for Human Security for the Aral Sea Region, established at the initiative of the Republic of Uzbekistan. The Multilateral Partnership for Human Security for the Aral Sea Region was established in partnership with a number of countries with the support and patronage of the UN to further improve the lives and livelihoods of people living in the Aral Sea region.